The Relationship Between Lifestyle and Dietary Patterns and the Incidence of Degenerative Diseases - Zaki Irwan; Muh Hasyim; Erdiawati Arief; Fahrul Islam; Fajar Akbar; Firman Firman (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Degenerative diseases, particularly diabetes mellitus and hypertension, contribute substantially to morbidity in Indonesia, including rural areas undergoing lifestyle transitions. Kalukku Subdistrict in Mamuju Regency is one such region, yet no comprehensive studies have examined the relationship between lifestyle, diet, and nutritional status with these diseases. This study aimed to analyze associations between lifestyle, dietary patterns, and nutritional status with the incidence of diabetes mellitus and hypertension in Kalukku Subdistrict. A cross-sectional design was applied to 150 purposively selected patients with diabetes mellitus and hypertension recorded at Tampapadang Health Center. Data were collected using lifestyle questionnaires, 24-hour dietary recalls, semi-quantitative food frequency questionnaires (SQ-FFQ), and anthropometric measurements. Associations were analyzed using chi-square tests with odds ratios (ORs) and 95% confidence intervals (CIs). Unhealthy lifestyle was strongly associated with diabetes mellitus (p<0.001, OR=12.17) and hypertension (p<0.001, OR=0.016, indicating 98.4% lower risk in individuals with healthy lifestyles). Unhealthy dietary patterns were associated with diabetes mellitus (p=0.040, OR=3.51) but not with hypertension (p=1.00). Nutritional status showed no significant relationship with either condition (p>0.05). Lifestyle is a key determinant of both diabetes mellitus and hypertension, while dietary patterns are associated only with diabetes mellitus. Nutritional status was not significantly linked to either disease. These findings highlight the importance of community-based health promotion and prevention, including daily physical activity through group exercise, dietary modification using local foods (corn, cassava, sweet potatoes) as alternatives to white rice, and salt-reduction campaigns via cooking demonstrations.